Early versus delayed enteral nutrition for neonatal hypoxic-ischemic encephalopathy undergoing therapeutic hypothermia: a randomized controlled trial - Ya Hu; Feng Chen; Xinyu Xiang; Fang Wang; Ziyu Hua; Hong Wei (Italian Journal of Pediatrics, 2022)
Abstract Background The practice of therapeutic hypothermia (TH) is widely used for neonatal hypoxic-ischemic encephalopathy (HIE) despite its corresponding feeding strategies are still controversial. This randomized controlled trial (RCT) demonstrated to evaluate the effect of early vs. delayed enteral nutrition on the incidence of feeding intolerance (FI) and other association during TH. Methods This single center, parallel-group, and no-blinded RCT was processed in a level III, and academic neonatal intensive care unit. Infants who were diagnosed with HIE and undertaken TH from September 2020 to August 2021 were enrolled. Participants were randomized to receive enteral nutrition either during TH/rewarming (early enteral nutrition, EEN) or after TH (delayed enteral nutrition, DEN) according to a recommend enteral feeding protocol. All data were analyzed using SPSS 26.0 software with a p-value< 0.05 was considered statistically significant. Results Ninety-two infants were enrolled after randomization, but 12 (13.04%) cases including 3 (3.26%) deaths were excluded from eventually analyzed, who did not initiate or discontinue the intervention. 80 cases (42 and 38 in the EEN and DEN group, respectively) who completed the interventions were eventually analyzed. Besides initial time of enteral feeds, two groups had processed the same feeding method. Total 23 (25.0%) cases developed FI, and no difference of morbidity was found between two groups (23.4% vs 26.7%, p = 0.595; Log Rank, p = 0.803). There was no case died or developed late-onset bloodstream and no difference of the incidence of hypoglycemia or weight gain was found (p > 0.05). The percentage of infants who had not reaching the goal of full enteral feeding volume between the two groups was similar (21.43% vs 23.68%, p = 0.809). The average time of parenteral nutrition, reaching full enteral feeds and hospital stay were shorter in the EEN group compared with the DEN group with significant differences (8.81 ± 1.67 vs 10.61 ± 2.06 days, p < 0.001; 9.91 ± 1.88 vs 12.24 ± 2.50 days, p < 0.001; 12.55 ± 4.57 vs 16.47 ± 5.27 days, p = 0.001 respectively). Conclusions Compared with delayed enteral nutrition, introduction of early enteral nutrition according to a recommend feeding strategy for neonatal HIE undergoing TH may be feasible and safe.FI is frequent in this high-risk group of infants which should not be ignored during feeding process. Trial registration The Chinese Clinical Trial Registry,ChiCTR2000038193, 2020-9-13, https://www.chictr.org.cn .